The Use of Oodlu to Improve Critical Thinking and Collaboration Skills of Fifth Graders at State of Elementary School Pasirhuni - Ita Rustiati Ridwan; Muhammad Hafeez; Susilawati; Putri Amalia Rahayu; Muhammad Hanif; Nenden Sundari (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
21st-century advances have influenced the education sector, so learning not only makes students excel but needs skills in dealing with the progress, the 4C skills. This research focuses on critical thinking and collaboration, and Indonesian is still considered one of the most important subjects. But the effort was still lacking. Students become passive, mingle less, and are not quite ready for progress. It is necessary to make efforts to use appropriate technology-based methods and media, using game-based learning with Oodlu. This research aims to know the use and the results of Oodlu's use in improving students' critical thinking and collaboration skills in Indonesian language learning. Using the CAR method of Kemmis and Mc. Taggart, test and observation, 30 students of V State of Elementary School (SD Negeri) Pasirhuni as the subjects. The results showed that students' skills improve in each cycle. Cycle I critical thinking of group 1 and group 3 40%, group 2 80%, group 1 collaboration was lacking, group 2 and group 3 were good. Cycle II critical thinking group 1 60%, group 2 80%, group 3 40%, collaboration group 1 was good, group 2 and group 3 were very good. Cycle III critical thinking of Group 1 and Group 3 80%, group 2 90%, the collaboration of Group 1 to Group 3 was very good. Thus the use of Oodlu in game-based learning can improve students' critical thinking and collaboration skills. This research implied that the Oodlu with GBL could be solutive to improving other relevant essential skills. Keywords: Improving Critical Thinking, Collaboration Skills, Oodlu